1993
DOI: 10.1002/ajh.2830440312
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐megakaryocyte interaction in bone marrow after high‐dose intravenous immunoglobulin therapy

Abstract: Localization of IgG in bone marrow after high-dose intravenous immunoglobulin therapy (IVIG) was investigated via light and electron microscopy. IgG was incorporated into the cytoplasm of various types of bone marrow cells of all the three lineages, particularly in reticulum cells, fat cells, and megakaryocytes. In addition, both reticulum cells and fat cells showed many elongated cytoplasmic protrusions, which were in contact with the various types of blood cells, especially the megakaryocytes. A filamentous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The commercial human IgG product (Venoglogulin-I®, Green Cross Co., Japan) was used for the therapy in which the following components were contained in 1 ml; 50 mg of IgG, 10 mg of albumin, 5 mg of polyethylene glycol 4000, 20 mg of D-mannitol and 5 mg of sodium chloride. The morphological observation of megakaryocytes in BM after IVIG of one male or one female patient in this study had been previously reported [7].…”
Section: Patients and Micesupporting
confidence: 53%
See 2 more Smart Citations
“…The commercial human IgG product (Venoglogulin-I®, Green Cross Co., Japan) was used for the therapy in which the following components were contained in 1 ml; 50 mg of IgG, 10 mg of albumin, 5 mg of polyethylene glycol 4000, 20 mg of D-mannitol and 5 mg of sodium chloride. The morphological observation of megakaryocytes in BM after IVIG of one male or one female patient in this study had been previously reported [7].…”
Section: Patients and Micesupporting
confidence: 53%
“…We observed the direct cell-to cell contact between macrophages and megakaryocytes [7] by immuno-electron microscopy in BM of an ITP-patient after IVIG and have also found to adhesion between RBC and EC by chance. These pictures had never been observed at…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“… 11 14 However, BM MΦs were reported to play both positive and negative roles in regulating megakaryopoiesis. 15 17 In patients with immune thrombocytopenia (ITP) who underwent intravenous immunoglobulin therapy, BM MΦs were found to closely contact MKs and were associated with increased platelet counts, suggesting that MΦs positively regulate megakaryopoiesis. 15 However, Alves-Rosa et al reported that depleting BM MΦs enhanced both megakaryopoiesis and platelet production in an ITP mouse model, which indicates that MΦs negatively regulate megakaryopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“… 15 17 In patients with immune thrombocytopenia (ITP) who underwent intravenous immunoglobulin therapy, BM MΦs were found to closely contact MKs and were associated with increased platelet counts, suggesting that MΦs positively regulate megakaryopoiesis. 15 However, Alves-Rosa et al reported that depleting BM MΦs enhanced both megakaryopoiesis and platelet production in an ITP mouse model, which indicates that MΦs negatively regulate megakaryopoiesis. 16 , 17 Typically, MΦs can be polarized into classically activated (M1) MΦs and alternatively activated (M2) MΦs, with distinct phenotypic and unique functional characteristics.…”
Section: Introductionmentioning
confidence: 99%